Peningkatan Akurasi Perhitungan IEEE C37.114 Double Ended Dengan Metode Selective Mode - Nidya Ayu Gusti Anggreani; Hamdani Hamdani; Reza Juliangga (Pusat riset dan Inovasi Nasional, 2026)
Rapid and precise handling in determining fault locations is essential to accelerate post-fault recovery and minimize economic losses caused by power outages. Several methods employed to identify fault locations include Single Ended and Double Ended analysis. This paper discusses the Selective Mode Double Ended Fault Locator Method, an enhancement of the IEEE C37.114 Double Ended method. This approach involves selecting maximum fault data values for Near Side (NS) and Far Side (FS) calculations, taking into account the differential or angle difference of the sequence between the two sides. The Double Ended calculation results from the total sample values are used to determine the mode, which serves as the final output of this Fault Locator method. This method is designed to identify faults and their locations with high accuracy and speed. Based on the research findings, the Selective Mode Double Ended (SMDE) method provides more accurate fault locator analysis compared to the Single Ended and Double Ended methods. The accuracy achieved with the Single Ended method is 90.9%, with the Double Ended method reaching 94.9%, and with the Selective Mode Double Ended (SMDE) method achieving 99.9%.